2015
DOI: 10.22610/jsds.v6i2.845
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Tax Revenue in Asean Countries

Abstract: Tax revenue is influenced by many factors. Existing studies reveal that political stability, level of corruption, quality of the policy, income per capita, share of agriculture to the GDP, and market openness are some of the factors influencing tax revenue. This study aims to analyze the influence of governance by using some indicators, such as political stability, government effectiveness, quality of regulation, law enforcement accountability and control on corruption in tax area through empirical analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
4
23
0
13
Order By: Relevance
“…The estimated negative coefficients in the short-run may be because the level of Political Stability and Absence of Violence documented in the given short time is not enough to produce a positive influence on the tax revenue. The significant long-run Political Stability and Absence of Violence is mostly consistent with the findings by Ajaz and Ahmad, (2010) and the Cukierman, Edwards and Tabellini (1991) cited in Syadullah and Wibowo (2015) earlier theoretical models who stressed that a higher degree of political instability and polarization causes a decrease in higher tax revenues. This finding conforms with the apriori expectation.…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 3 more Smart Citations
“…The estimated negative coefficients in the short-run may be because the level of Political Stability and Absence of Violence documented in the given short time is not enough to produce a positive influence on the tax revenue. The significant long-run Political Stability and Absence of Violence is mostly consistent with the findings by Ajaz and Ahmad, (2010) and the Cukierman, Edwards and Tabellini (1991) cited in Syadullah and Wibowo (2015) earlier theoretical models who stressed that a higher degree of political instability and polarization causes a decrease in higher tax revenues. This finding conforms with the apriori expectation.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…The instability in government by way of overthrowing a government, the higher the political tension and the incidence of terrorist acts which invariably will cause lower tax collection (Ajaz and Ahmad, 2010). This is in tandem with theoretical models built by Cukierman, Edwards and Tabellini (1991) cited in Syadullah and Wibowo (2015), where political instability and polarization determine the equilibrium effectiveness of the tax system and the arrangement occasioned by tax revenues. They offer evidence in support of a model that shows that a high degree of political instability and polarization leads to a decrease in high tax revenues.…”
Section: Political Stability and Absence Of Violence And Tax Revenuementioning
confidence: 68%
See 2 more Smart Citations
“…Rosid, Evans, and Tran-Nam (2017) opined that corruption is perceived to be high in most developing countries and this affect taxpayer's perception of trust in government and willingness to pay tax. Syadullah and Wibowo (2015) also reported that, most developing countries suffered tax revenues losses due to bribery and corruption, this is achieved through a form of dishonest or immoral behaviour. Trust is linked to perception of corruption.…”
Section: Control Of Corruptionmentioning
confidence: 99%